CORRECTION OF BLUE SWIMMING CRAB FOLDING TRAP ENTRANCE: KOREKSI PINTU MASUK BUBU LIPAT RAJUNGAN - Defra Monika Nasution; Gondo Puspito; Didin Komarudin; Mustaruddin Mustaruddin; Deni Aulia (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2025)
Folding crab traps are widely used by Indonesian fishermen because they are easy to construct and operate. Observations suggest that crabs frequently struggle to pass through the entrance channel, as their legs become entangled in the mesh. The spines on the sides of their bodies usually become entangled in the net threads because the entrance is too narrow. Consequently, the chance of crabs being trapped is very low. The objective of the study is first to determine the combination of slope angle and mesh size for the channel that allows for crabs to pass through easily. The study attempted to combine the traverse angles of 20°, 30°, and 40° with mesh sizes of 0.125